Pharmacogenetic and pharmacokinetic factors for dexmedetomidine-associated hemodynamic instability in pediatric patients - Guan, Yanping; Li, Bilian; Zhang, Yiyu; Luo, Hao; Wang, Xueding; Bai, Xue; Zheng, Zhuoling; Huang, Yaying; Wei, Wei; Huang, Min; Song, Xingrong; Zhong, Guoping (Frontiers in Pharmacology, 2025)
Purpose The incidence of hemodynamic instability associated with dexmedetomidine (DEX) sedation has been reported to exceed 50%, with substantial inter-individual variability in response. Genetic factors have been suggested to contribute significantly to such variation. The aim of this study was to identify the clinical, pharmacokinetic, and genetic factors associated with DEX-induced hemodynamic instability in pediatric anesthesia patients. Methods A cohort of 270 pediatric patients scheduled for elective interventional surgery received an intranasal dose of 3 mcg·kg-1 of dexmedetomidine, and subsequent propofol induction was conducted when patients had a UMSS of 2–4. The primary endpoint was hemodynamic instability—defined as a composite of hypotension and/or bradycardia, which is characterized by a 20% reduction from age-specific baseline values. Plasma concentrations of dexmedetomidine were determined, and single-nucleotide polymorphisms (SNPs) were genotyped. A validated population pharmacokinetic model was used to estimate pharmacokinetic parameters. LASSO regression was used to identify significant factors, and a Cox’s proportional hazards model-derived nomogram for hemodynamic instability was developed. Results Hemodynamic instability was observed in 52 out of 270 patients (209 events), resulting in a cumulative incidence of 16.30% at 90 min, as estimated by Kaplan–Meier estimation, and it was associated with a median time to event of 35 min. The interval time between DEX initiation and propofol induction was 16 min (IQR: 12–22 min). The cumulative incidence was 8.2% within 22 min after DEX initiation. The identified significant risk factors for DEX-associated hemodynamic instability included weight, DEX clearance, concomitant propofol use, and the following gene variants UGT2B10 rs1841042 (hazard ratio (HR):1.41, 95% confidence interval (CI): 1.12–1.79), CYP2A6 rs8192733 (HR:0.28, 95%CI:0.09–0.88), ADRA2B rs3813662 (HR:1.39,95%CI:1.02–1.89), CACNA2D2 rs2236957 (HR:1.46, 95%CI:1.09–1.96), NR1I2 rs3814057 (HR:0.64, 95%CI:0.43–0.95), and CACNB2 rs10764319 (HR:1.40,95%CI:1.05–1.87). The areas under the curve for the training and test cohorts were 0.881 and 0.762, respectively. The calibration curve indicated excellent agreement. Conclusion The predictive nomogram, which incorporates genetic variants (UGT2B10, CYP2A6, ADRA2B, CACNA2D2, NR1I2, and CACNB2) along with clinical factors such as weight, DEX clearance, and propofol use, may help prevent DEX-associated hemodynamic instability. Delayed hemodynamic instability is likely to occur after 35-min DEX initiation in patients with lower DEX clearance after propofol induction.